Loose change 2nd ed. - Avery, Dylan; Rowe, Korey; Louder Than Words (firm) ([S.l.] : Louder Than Words ; Kuala Lumpur : Saba Islamic Media (distributor), 2006)
This film is the follow up to the most provocative 9-11 documentary that shows direct connection between the attacks of September 11, 2001 and the United States government. Evidence is derived from news footage, scientific fact, and the most important, Americans who suffered through that tragic day
Title from title screen
Music Nick Tha Ida, Swae, Smoke, Skooly